Demographics, disease severity, and per patient cost of melioidosis in East Coast and Northern Malaysia:A hospital-based retrospective cohort study from 2019 to 2023 (Journal of Medicine, 2026)
Objectives: To examine the demographics, disease severity, hospital stay duration, intensive care unit (ICU) stay, and per-patient cost (PPC) of melioidosis cases in Eastern and Northern Malaysia.Methods: A total of 502 patients in six hospitals in Eastern and Northern Malaysia were included in the study. Descriptive statistics were used to analyze patient demographics, disease severity, comorbidities, length of stay (LOS), and ICU stay. One-way ANOVA and Kruskal-Wallis tests were applied to compare LOS and ICU stay based on comorbidities. Pearson chi-square test was used to identify the association between comorbidities and severity.Results: LOS and ICU duration were significantly influenced by comorbidity burden (P